Strengthening Fraud Prevention in Islamic Banks: The Roles of Islamic Corporate Governance, Sharia Compliance, and Internal Control - Mutmainnah, Andi; Amiruddin; Sudirman; Syaharuddin; Sumarlin (Al-Kharaj: Journal of Islamic Economic and Business, 2025)
This study aims to examine the influence of Islamic Corporate Governance (ICG) and Sharia Compliance on fraud prevention with Internal Control as a moderating variable in Islamic Commercial Banks in Indonesia for the period 2016 to 2024. This study uses a quantitative approach with 90 observations from 10 banks selected through a purposive sampling method. Sharia Compliance is measured using two proxies, namely the Islamic Income Ratio (IsIR) and the Profit Sharing Ratio (PSR). Data were obtained from annual reports, financial statements, and Good Corporate Governance (GCG) reports, then analyzed by Moderated Regression Analysis (MRA) using E Views 12 software. The results show that ICG has a negative but insignificant effect on fraud prevention, IsIR has a significant positive effect, and PSR has a significant negative effect. The moderating role of Internal Control produces varying findings, namely insignificant in the relationship between ICG and fraud, significant negative in the relationship between IsIR and fraud, and significant positive in the relationship between PSR and fraud. The novelty of this research lies in its comprehensive approach, integrating governance, sharia compliance, and internal control into the analysis of fraud prevention in Islamic banking. The results provide theoretical contributions to the literature on sharia governance and provide practical input for Islamic banking in strengthening transparency, accountability, and risk management.